2020
DOI: 10.15252/embj.2019103949
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated demethylation of H3K9 and H3K27 is required for rapid inflammatory responses of endothelial cells

Abstract: Histone H3 lysine‐9 di‐methylation (H3K9me2) and lysine‐27 tri‐methylation (H3K27me3) are linked to repression of gene expression, but the functions of repressive histone methylation dynamics during inflammatory responses remain enigmatic. Here, we report that lysine demethylases 7A (KDM7A) and 6A (UTX) play crucial roles in tumor necrosis factor (TNF)‐α signaling in endothelial cells (ECs), where they are regulated by a novel TNF‐α‐responsive microRNA, miR‐3679‐5p. TNF‐α rapidly induces co‐occupancy of KDM7A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 92 publications
(167 reference statements)
2
28
0
Order By: Relevance
“…UTX has been functionally linked to many physical and pathological processes, including embryonic development, 39 , 40 tumor progression, 41 , 42 , 43 , 44 inflammation, 45 and stem cell differentiation 46 , 47 by H3K27 demethylation-dependent or -independent gene transcription. Although UTX was shown to be required for nuclear factor κB (NF-κB)-dependent inflammatory response of ECs, 48 the regenerative regulation mediated by UTX in SCI is still unclear. We first examined the changes of several key epigenetic regulators post SCI, and we found that the mRNA level of UTX increased significantly post SCI, whereas the changes of other epigenetic factors are variable at different time points post SCI.…”
Section: Discussionmentioning
confidence: 99%
“…UTX has been functionally linked to many physical and pathological processes, including embryonic development, 39 , 40 tumor progression, 41 , 42 , 43 , 44 inflammation, 45 and stem cell differentiation 46 , 47 by H3K27 demethylation-dependent or -independent gene transcription. Although UTX was shown to be required for nuclear factor κB (NF-κB)-dependent inflammatory response of ECs, 48 the regenerative regulation mediated by UTX in SCI is still unclear. We first examined the changes of several key epigenetic regulators post SCI, and we found that the mRNA level of UTX increased significantly post SCI, whereas the changes of other epigenetic factors are variable at different time points post SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancer–promoter interactions play an important role in the control of gene transcription. A distal enhancer simultaneously modulating the expression of multiple genes encoding CXCL chemokines has been identified by high-throughput screening but not functionally verified until recently in HUVEC cells 29 , 30 . We hypothesized the presence of a super-enhancer regulating the expression of chemokines CXCL1 , 6 , and 8 under the control of TNFα, and utilized circular chromosome conformation capture-sequencing (4C-Seq) as a discovery tool to identify this putative CXCL master regulatory element in LSEC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Later, two histone demethylases, KDM7A and KDM6A (UTX), were identified as hsa-miR-3679-5p direct targets in monocytes. Downregulation of these genes by hsa-miR-3679-5p led to the reduction of adhesion molecules and regulation of monocyte adhesion to endothelial cells, which could be linked to an inflammatory response ( 56 ). Future studies are needed to prove whether these processes are relevant to ARVC.…”
Section: Discussionmentioning
confidence: 99%